Education in the Post-Pandemic Era: Indigenous Children and Youth - Cherubini, Lorenzo (The International Indigenous Policy Journal)

(untitled) (Scholarship@Western (Western University), 2020)
The COVID-19 pandemic crisis resulted in more than 100 countries legislating school closures in March 2020. In response, provincial ministries and their respective publicly funded school boards have implemented online learning platforms to avoid disruptions to student learning. For students already ostracized in public education, on-line learning may serve to further embed them in the proverbial margins. This editorial speaks to the urgency for educators at all levels to prepare for the potentially devastating outcomes on Indigenous student learning and progress in post-pandemic public schools and classrooms. The preparation for these realities has to be both immediate and retrospective given the complexities of these unique circumstances that have created interwoven layers of marginalization for Indigenous students.